THE ORIGINS AND FOUNDERS OF THE CLASSIFICATION OF TAWHID (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes, based on scholarly sources, the historical formation of tawhid, the central concept of Islamic belief, and the emergence of the idea of dividing it into categories such as rububiyyah, uluhiyyah, and asma wa sifat. It explains that during the time of the earliest Muslims and the righteous salaf as salih, tawhid was understood as a unified concept of faith, and there was no practice of dividing it into separate terminological sections. The classification of tawhid as a theoretical system mainly developed during the period of Ibn Taymiyyah and was later turned into a doctrinal and practical standard by his students and the Wahhabi movement. The study emphasizes that the disagreement lies not in the classification itself, but in the detailed interpretations and in using it as a tool for issuing religious judgments. In particular, the absolutization of this classification has led to the increase of takfir, religious violence, and conflicts within Muslim societies, as shown by academic evidence. The article presents the balanced position of Sunni scholars and highlights the necessity of preserving the historical unity of tawhid.
Keywords: tawhid; classification of tawhid; rububiyyah and uluhiyyah; salaf as salih; Ibn Taymiyyah; Wahhabi movement